Efficacy of Chlorogenic Acid in Treating Tripterygium Glycoside-Induced Asthenozoospermia in Rats and Its Possible Mechanisms - Long Chen; God’spower Bello-Onaghise; Mo Chen; Shunda Li; Yu Zhang; Haoran Wang; Qianwei Qu; Yanhua Li (Veterinary Sciences)
Tripterygium glycosides (TGs) are the most common form of traditional Chinese medicine, known as Tripterygium wilfordii Hook F (TWHF) [...]